Computerisation of a police department in a state in Western India - Verma, Sanjay, (SAGE Knowledge. Cases., 2015)
Mr. Ajay Vasav, Inspector General of Police of ASWI (A state in Western India) shared his apprehensions about the computerisation process in the state. This initiative was being taken when the Government of India had envisaged a centralised crime and criminal tracking system to harness the power of information technology.